P1357SODIIUM BICARBONATE CAN REPLACE THE HEPARIN AS "CATHETER LOCK SOLUTION" OF CENTRAL CATHETERS (CVC) FOR HEMODIALYSIS (HD)?. (6th June 2020) - Corciulo, Roberto; Zazzera, Pierfelice; Misceo, Fernanda; Corciulo, Simone; Lomonte, Carlo; Libutti, Pasquale
Abstract: Background and Aims: The CVC often faces thrombosis and/or infection and currently there are no interventions that guarantee the efficiency of the CVC and the absence of bacterial infections. Recently Adel S. El-Hennawy et al. NDT, 2019, have shown that the use of sodium bicarbonate as "catheter lock solution" (SBCLS) in HD patients has a local anticoagulant effect and reduces the frequency of thrombosis and infections. Therefore, we wanted to use SBCLS in the management of our dialysis patients who needed HD treatment through CVC. Method: The study included n. 15 HD patients (8M and 7F) with a CVC (see tab.1), whose CVC were previously medicated with heparin or citrate. At the time of the introduction of the SBCLS, patients showed no signs of CVC thrombosis or bacteremia; 2 patients had previously had haemorrhagic complications, 3 had malfunctioning thrombotic CVC. The observation period was 2379 days (mean 158 ± 50). Upon the conclusion of HD treatment, each port of all two-port catheters was flushed and locked with 10 mL of SBCLS (NaHCO3 at 8.4% -pH 7-8.5) and approximately 2 mL of the injected solution remained locked within the catheter. One patient who was allergic to heparin was included in the study. Results: At the end of the study, only 3 patients had thrombotic problems with CVC and none had infections. However, none of the enrolled patients had to replace the CVC. The treatment was well tolerated by all patients who did not present complications. Conclusion: In our short and brief experience, SBCLS has proved effective and safe in the prevention of thrombosis and infection of CVC. SBCLS appears to be an effective alternative to heparin and citrate in the management of CVC in the absence of bleeding complications. Finally SBCLS is a valid medical solution in patients allergic to heparin.